Biventricular Mechanical Circulatory Support Does Not Prevent Delayed Myocardial Ventricular Rupture following Myocardial Infarction - Yazhini Ravi; Emily P. Sudhakar; Pratima Nayak; Chittoor B. Sai-Sudhakar; Konstantinos Dean Boudoulas (Case Reports in Cardiology)
Cardiogenic shock and myocardial rupture can complicate an acute myocardial infarction (AMI). A case is reported in which a 58-year-old male with an acute inferior myocardial infarction required placement of biventricular assist device for hemodynamic support eight days after the onset of his AMI; eleven days after his AMI, the patient developed abrupt onset of hemodynamic instability with massive bleeding from his chest tube due to delayed free wall myocardial rupture that was discovered when he was taking emergently to the operating room. Myocardial rupture in patients with a ventricular assist device should be considered in the differential diagnosis in the event of acute hemodynamic compromise. A high level of suspicion for such a complication should prompt aggressive and emergent actions including surgery. We present a case of delayed free wall myocardial rupture following an acute inferior wall myocardial infarction in a patient with biventricular mechanical circulatory support.